2021
DOI: 10.56093/ijas.v91i7.115117
|View full text |Cite
|
Sign up to set email alerts
|

Determination of agricultural infrastructural suitability in aspirational districts: A case study of Bundelkhand

Abstract: Agricultural infrastructure has the potential to transform subsistence farming into commercial and dynamic farming system. Adequate markets, roads, irrigation, extension services, credit facilities, storage etc. facilitate lowering of farming costs and increase in farm income. The study, carried out during 2017-20 at ICAR-NIAP, presents methodology for measuring adequacy status of rural infrastructure and its categorisation into five classes using a case study of Bundelkhand region.The results show that there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Among the input parameters, the most important parameters were soil (soil texture, drainage, soil depth, pH, OC and EC), climate (temperature and rainfall) and topography (slope) for cropland suitability assessment. In recent study Jain et al (2021a) demonstrated the methodology for computation of infrastructural suitability in agriculture at district, state and country level. Composite infrastructural classes highlighted that all the states in the country have infrastructural inadequacy in one or more parameters (Jain et al 2021b).…”
Section: Integration Of Mce and Geospatial Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the input parameters, the most important parameters were soil (soil texture, drainage, soil depth, pH, OC and EC), climate (temperature and rainfall) and topography (slope) for cropland suitability assessment. In recent study Jain et al (2021a) demonstrated the methodology for computation of infrastructural suitability in agriculture at district, state and country level. Composite infrastructural classes highlighted that all the states in the country have infrastructural inadequacy in one or more parameters (Jain et al 2021b).…”
Section: Integration Of Mce and Geospatial Techniquesmentioning
confidence: 99%
“…In recent study Jain et al (2021a) demonstrated the methodology for computation of infrastructural suitability in agriculture at district, state and country level. Composite infrastructural classes highlighted that all the states in the country have infrastructural inadequacy in one or more parameters (Jain et al 2021b). The authors analyzed that improvement in agricultural infrastructure in the country calls for huge investments to enhance the income of the farmers.…”
Section: Integration Of Mce and Geospatial Techniquesmentioning
confidence: 99%